2023
DOI: 10.1530/eor-23-0016
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid-induced focal convulsions after spinal surgery: a rare case report and literature review on side effects of accidental spinal administration of tranexamic acid

Abstract: Convulsions are a neurological illness that has complexity. In clinical treatment, drug-induced convulsions appear from time to time. Drug-induced convulsions often begin as isolated acute seizures but may progress to persistent seizures. In orthopedics, topical administration of tranexamic acid is commonly used in conjunction with intravenous drip to achieve hemostasis during artificial joint replacement surgery. However, side effects induced by tranexamic acid accidental spinal administration should be taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Wang and colleagues express concern that topical TXA can enter the intrathecal sac in the setting of dural and arachnoid tears, leading to adverse neurological events. 8 This concern was also raised in our review. However, our meta-analysis of 2045 patients revealed no reported neurological events.…”
Section: Responsementioning
confidence: 71%
See 1 more Smart Citation
“…Wang and colleagues express concern that topical TXA can enter the intrathecal sac in the setting of dural and arachnoid tears, leading to adverse neurological events. 8 This concern was also raised in our review. However, our meta-analysis of 2045 patients revealed no reported neurological events.…”
Section: Responsementioning
confidence: 71%
“…Such cases have already occurred in clinical applications. 8,9 In such cases, the potential neurotoxic and epileptogenic properties associated with topical TXA could pose a real danger that leads to life-threatening conditions such as seizures or arrhythmias, significantly increasing morbidity and mortality.Moreover, in terms of the efficacy of TXA, many studies in recent years have shown that the use of local TXA…”
mentioning
confidence: 99%
“…In our pooled results, there were five cases of thrombosis-related complications in the TXA group and nine in the control group, with no marked difference between the two groups. Luo et al found that use of TXA in spine surgery may induce epilepsy ( 36 ), and the incidence of convulsions increased from 0.5–1.0% to 6.4–7.3% with administration of TXA 50–100 mg/kg in cardiac surgery ( 37 ). No convulsion-related complications were reported in the studies included in our meta-analysis and review.…”
Section: Discussionmentioning
confidence: 99%
“…However, Luo et al reported a case of persistent convulsions in both lower extremities after topical tranexamic acid. After analysis, it is considered that high concentrations of tranexamic acid entering the cerebrospinal fluid led to direct inhibition of γ-aminobutyric acid and glycine receptors in the posterior site of neurons in the dorsal horns of the spinal cord, thereby increasing excitability and leading to the development of persistent convulsions in patient ( 31 ). TLIF is prone to damage to the dura because it is performed next to the dura.…”
Section: Discussionmentioning
confidence: 99%